Robotics: Science and Systems VIII 2012
DOI: 10.15607/rss.2012.viii.049
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Testbed for Robotic Neuromuscular Controllers

Abstract: Abstract-Current control approaches to robotic legged locomotion rely on centralized planning and tracking or motion pattern matching. Central control is not available to robotic assistive devices that integrate with humans, and matching predefined patterns severely limits user dexterity. By contrast, biological systems show substantial legged dexterity even when their central nervous system is severed from their spinal cord, indicating that neuromuscular feedback controls can be harnessed to encode stability,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…This step will enable indirect verification of the control by comparing predicted and observed muscle actuations in disturbed human swing phases. In addition, we plan to transfer the control to robotic legs in humanoid and rehabilitation robotics, for which we are currently developing a robotic leg testbed [28].…”
Section: Discussionmentioning
confidence: 99%
“…This step will enable indirect verification of the control by comparing predicted and observed muscle actuations in disturbed human swing phases. In addition, we plan to transfer the control to robotic legs in humanoid and rehabilitation robotics, for which we are currently developing a robotic leg testbed [28].…”
Section: Discussionmentioning
confidence: 99%
“…Since then, numerous research studies have been implemented on the co-contraction of antagonistic muscle control, which have proven its ability to increase the stiffness and stability at the joints during volitional movements [75][76][77][78][79][80][81][82][83][84][85][86]. Based on these research studies, it was shown that by utilizing information from the antagonistic muscle co-contraction, muscular activation levels could be manipulated to control the movements of the joints.…”
Section: Co-contraction Of Antagonistic Muscle Controlmentioning
confidence: 99%
“…Furthermore, analyses on the implementation of mono-and bi-articular actuators for achieving the high muscle moment required at the joints and better gait trajectories were also taken into consideration in real practice [91][92][93][94][95]. The study of antagonistic muscle co-contraction suggested that the control of the orthosis, which implements these mono-and bi-articular actuators, could achieve good joint stiffness and stability [75][76][77][78][79][80][81][82][83][84][85][86]. The design was biologically inspired (by human muscles), as it employed two compliant elements to manipulate the joints.…”
Section: Simulation Of the Co-contraction Model For Antagonistic Musclesmentioning
confidence: 99%
“…We target NLSs for SEAs in a neuromuscular gait testbed [21]. The NLSs for these SEAs must generate an exponentially stiffening torque with a zero torque at zero deflection, and a maximum torque τ max = 5Nm at ∆θ = ∆θ max .…”
Section: A Torque Profile Optimizationmentioning
confidence: 99%